2005
DOI: 10.1177/0363546504271503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drain Placed in the Donor Site in the Early Postoperative Period after Arthroscopically Assisted Anterior Cruciate Ligament Reconstruction with Quadrupled Hamstring Tendons

Abstract: Drain placement at the donor site after anterior cruciate ligament reconstruction gives more comfort to the patient and provides better flexion within the first week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Patients receiving a postoperative drain reported significantly higher VAS scores in one trial, 30 significantly lower VAS scores in another trial, 60 and no significant differences in VAS scores or analgesic consumption in a third trial 80 when compared to no drain. All 3 studies reported no complications associated with the use of drains.…”
Section: Surgical Technique (Table 8)mentioning
confidence: 90%
“…Patients receiving a postoperative drain reported significantly higher VAS scores in one trial, 30 significantly lower VAS scores in another trial, 60 and no significant differences in VAS scores or analgesic consumption in a third trial 80 when compared to no drain. All 3 studies reported no complications associated with the use of drains.…”
Section: Surgical Technique (Table 8)mentioning
confidence: 90%
“…5,6 Usually bleeding in case of ACL reconstruction occurs at intraarticular site as well as the graft donor site (hamstring or Bone patellar bone tendon graft) which adds to the formation of the knee effusion post operatively. 7 Various ways of reducing the bleeding and formation of effusion involves use of tourniquet, drains, or antifibrinolytic chemotherapeutic agents like Inj Tranexamic acid (TXA).…”
Section: Introductionmentioning
confidence: 99%
“…5 Two common bleeding sources were identified mainly from intra-articular femoral or tibial tunnels and harvested graft sites. 6 Some surgeons advocate placing a drain at the surgical site prior to skin closure but multiple randomised controlled trials (RCTs) have proven this technique to be ineffective in the reduction of haemarthrosis in ACLR surgery. [6][7][8][9] Tranexamic acid (TXA) is a synthetic analogue of lysine, which acts as a competitive inhibitor at the plasminogen lysine-binding site to reduce postoperative bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…6 Some surgeons advocate placing a drain at the surgical site prior to skin closure but multiple randomised controlled trials (RCTs) have proven this technique to be ineffective in the reduction of haemarthrosis in ACLR surgery. [6][7][8][9] Tranexamic acid (TXA) is a synthetic analogue of lysine, which acts as a competitive inhibitor at the plasminogen lysine-binding site to reduce postoperative bleeding. 10 It is believed that the use of TXA reduced postoperative blood loss and incidence of severe haemarthrosis in patients undergoing ACLR surgery.…”
Section: Introductionmentioning
confidence: 99%